SOSIALISASI MATERI SARANA PERKERETAAPIAN PADA GENERASI MILENIAL (JPMPPI (Jurnal Pengabdian Masyarakat), 2023)
The purpose of this service is to provide socialization to the millennial generation regarding railway facilities. The method used is in the form of planning, implementation, and evaluation. Planning in the form of choosing a location in Malangi, participants from the millennial generation and making materials, Implementation in the form of lectures given to participants, Evaluation carried out in this community service in the form of giving pre-test and post-test to participants to get results before being given the material and after being given the material. Based on the results of the posttest, it was found that the participants could understand the material of the railway facilities well, with an average pretest score of 38.75 and the post-test results obtained 94.37